P.036 Targeted molecular therapy with quinidine for seizures in a neonate with KCNT1 mutation leads to poor response. (2nd June 2017) - Smith, JM; Patel, M; Xu, Q; Uliel-Sibony, S; Demos, M; Connolly, M; Datta, A; Looned, L
Abstract : Background: The KCNT1 gene encodes subunits of the Na+-activated K+ channel, widely expressed in the CNS. Mutations of this gene have been implicated in Malignant Migrating Partial Seizures of Infancy (MMPSI). This early-onset epileptic encephalopathy represents a challenge due to pharmacoresistance. The channel-specific mutation represents the potential for targeted pharmacotherapy. Quinidine is a partial antagonist of the KCNT1 encoded channel; patients with MMPSI have been reported to have responded to doses ranging 34.4/kg/d - 60mg/kg/d. We present a case of MMPSI with a KCNTI mutation (c.G1283A:p.R428Q) trialled on quinidine.Methods: Following ineffective trials of 6 anti-seizure medications, this patient was trialled on oral quinidine. This patient was titrated up to a dose of 52mg/kg/d. Twenty-four hour EEG monitoring prior to quinidine therapy, and at target dose were compared.Results: Prior to initiation of quinidine, this patient experienced 22 electrographic seizures over 24 hours. At target dose, this patient experienced greater than 70 seizures over 24 hours.Conclusions: Quinidine has previously been reported to be effective in patients with MMPSI with the same and different mutations. We report the second case of a patient with MMPSI and KCNT1 mutation R428Q with poor clinical response to quinidine.